Manajemen Kegiatan Ekstrakulikuler Pendidikan Anak Usia Dini Pada Kelompok Kelompok Bermain - ., Rana; ., Retno Wulandari; ., Fahmi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Education is an important future investment. To educate the life of the nation, a good strategic plan is needed. Education can be divided into three types, namely formal, non-formal, and informal. The implementation of extracurricular activities in PAUD often faces obstacles in its management. Therefore, the management of extracurricular activities in PAUD must be managed seriously. Proper management will have a positive impact on the quality of PAUD. This study uses a qualitative descriptive method with data collection through literature study. Literature study is a data collection technique by seeking information through scientific journals, reference books, and publications available in libraries.